2017
DOI: 10.1136/bmjsem-2016-000156
|View full text |Cite
|
Sign up to set email alerts
|

Reduced muscular fatigue after a 12-week leucine-rich amino acid supplementation combined with moderate training in elderly: a randomised, placebo-controlled, double-blind trial

Abstract: BackgroundAge-related muscle loss is characterised by a progressing decrease in muscle mass, strength and function. Besides resistance training and physical activity, appropriate nutrition that is rich in protein, especially branched-chain amino acids, is very important to support training effects and positively influence the protein synthesis to degradation ratio.AimThe purpose of this study was to evaluate the effect of a 12-week leucine-rich amino acid supplementation in combination with moderate training.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…This effect was ameliorated by leucine supplementation, which decreased CK-MB concentration and suggested a protective role of leucine. This protection may be linked to anabolic or anti-catabolic effects on protein metabolism, as reported in previous studies ( Canedo et al, 2010 ; Murphy et al, 2016 ; Reule et al, 2017 ).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This effect was ameliorated by leucine supplementation, which decreased CK-MB concentration and suggested a protective role of leucine. This protection may be linked to anabolic or anti-catabolic effects on protein metabolism, as reported in previous studies ( Canedo et al, 2010 ; Murphy et al, 2016 ; Reule et al, 2017 ).…”
Section: Discussionsupporting
confidence: 69%
“…Despite not finding differences in CK concentrations, Reule et al (2017) observed greater effort tolerance and strength maintenance in a group of aged, untrained, leucine-supplemented elderly subjects subjected to a fatigue protocol through exercise when compared to the placebo group. These results agree with the findings of the present study, since the group of rats supplemented with leucine did not show decreased performance even in experimental hyperthyroidism, which according to Silva ( Argov et al, 1988 ), can simulate the muscular damage caused by physical exercise.…”
Section: Discussionmentioning
confidence: 58%
“…However, CK and DOMS were not differentially affected by the supplementation. Although some studies demonstrated reduced CK after a damaging exercise in groups supplemented with proteins ( Jackman et al, 2010 ; Howatson et al, 2012 ), most of the reports available in the literature show no difference between placebo- and protein-fed groups after exercise ( Eddens et al, 2017 ; Reule et al, 2017 ), which is consistent with the present results.…”
Section: Discussionsupporting
confidence: 91%
“…The differential effects of the supplements were particularly clear when considering the recovery kinetics of the concentric power, which were accelerated in the participants supplemented with proteins, and especially NW, which promoted short-term recovery. NW is a leucine-rich supplement and interestingly, Reule et al (2017) recently reported that a leucine-rich amino-acid supplementation, combined to moderate training, improved short-term recovery after a damaging exercise at the end of a training period. Similarly, two studies demonstrated that NW reduced exercise-induced fatigability when combined with a training program in young ( Babault et al, 2014 ) or elderly men ( Gryson et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, stress models (joint or muscle related) have been used in the past to induce standardized load on physical structures to be able to observe changes on perceived stress as accurately as possible [ 8 – 10 ]. For the observation of knee joint function, different joint bearing movements are qualified to be used during a stress model.…”
Section: Introductionmentioning
confidence: 99%